The concept of thromboinflammation underlying thrombotic complications, tumor progression and metastasis in gynecological cancer patients - A. D. Makatsariya; E. V. Slukhanchuk; V. O. Bitsadze; A. G. Solopova; J. Kh. Khizroeva; L. A. Ashrafyan; V. N. Serov; A. Е. Voynovskiy; J. Yu. Ungiadze; A. V. Lazarchuk; M. V. Tretyakova; N. A. Makatsariya; et al. (Акушерство, гинекология и репродукция)
The results of recent studies show that tumor biology, coagulation activation, and inflammatory reactions profoundly contribute to the thrombosis pathogenesis in cancer as well as tumor progression, metastasis, and developing chemoresistance. Cancer is an independent predictor of thrombosis. During carcinogenesis, tumor cells express proinflammatory cytokines, proangiogenic and procoagulant factors, and also stimulate other cells to express various components promoting emerging thromboinflammation. The discovery of neutrophil extracellular traps (NETs) provides an opportunity to take a new look at biology and a role neutrophils may play in thromboinflammation and tumorigenesis. The close interplay between tumor cells, tumor-associated neutrophils and NETs as well as other players in the tumor microenvironment underlies activation of thromboinflammation in cancer patients not only resulting in thrombus formation, but also promoting tumor growth and dissemination.